Encyclopedia of Clinical Neuropsychology (Springer International Publishing, 2018)
The Encyclopedia of Clinical Neuropsychology is the first and only encyclopedia covering assessment, treatment, and rehabilitation of adult and pediatric neuropsychological disorders. The new and revised 2nd edition includes 100 new entries and extensive updates and revisions. Clinical neuropsychology is a rapidly evolving specialty whose practitioners serve patients with traumatic brain injury, stroke and other vascular impairments, brain tumors, epilepsy and nonepileptic seizure disorders, developmental disabilities, progressive neurological disorders, HIV- and AIDS-related disorders, and dementia. Services include evaluation, treatment, and case consultation in child, adult, and the expanding geriatric population in medical and community settings. The clinical goal always is to restore and maximize cognitive and psychological functioning in an injured or compromised brain. Most neuropsychology reference books focus primarily on assessment and diagnosis, and to date none has been encyclopedic in format. Clinicians, patients, and family members recognize that evaluation and diagnosis is only a starting point for the treatment and recovery process. During the past decade there has been a proliferation of programs, both hospital- and clinic-based, that provide rehabilitation, treatment, and treatment planning services. This encyclopedia will serve as a unified, comprehensive reference for professionals involved in the diagnosis, evaluation, and rehabilitation of adult patients and children with neuropsychological disorders. From the reviews of the first edition: "This a A to Z approach to defining clinical psych and clinical neuropsychology terms. ... recommend this as a reference for Clinical Neuropsychologists." Joseph J. Grenier, Amazon.com, February, 2014 "An indispensable four-volume reference series, which both established and up-and-coming neuropsychologists will find to be an invaluable addition to their clinical practice. Clinicians across a broad range of settings ... will find it to be a comprehensive reference guide. ... Each entry provides cross-references to related topic areas within the series, as well as additional readings, for the interested reader to use as a springboard to expand their understanding of each topic area." Sarah E. Bullard, Mélina Griss, Sonia Greene and Anna Gekker, Archives of Clinical Neuropsychology, November, 2012 "This book is the most comprehensive text ever published in the field of clinical neuropsychology. ... If I had to select only one book to have on my desk, in my office, this would be the one." Amazon.com, December, 2010.